2017
DOI: 10.1007/s11356-017-0802-8
|View full text |Cite
|
Sign up to set email alerts
|

Modification of chitosan/calcium alginate/Fe3O4 hydrogel microsphere for enhancement of Cu(II) adsorption

Abstract: Copper in drinking water causes a significant environmental problem. Composite material based on alginate hydrogel has been gaining attention in the field of Cu(II) adsorption. However, alginate-based hydrogel exhibits poor mechanical property and relative low adsorption capacity which limit their application. The present study is devoted to the modification of chitosan/calcium alginate/FeO (CAF) hydrogel microsphere by NaOH solution for enhancement of Cu(II) adsorption. Results reveal that modification of CAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, after the adsorption process, Zn/CANPs and Cu/CANPs became smoother and less porous. These images demonstrated that metal ions were adsorbed by CANPs through their pores [23]. Furthermore, the ability of CANPs to adsorb metal ions was validated using EDX.…”
Section: Resultsmentioning
confidence: 86%
“…However, after the adsorption process, Zn/CANPs and Cu/CANPs became smoother and less porous. These images demonstrated that metal ions were adsorbed by CANPs through their pores [23]. Furthermore, the ability of CANPs to adsorb metal ions was validated using EDX.…”
Section: Resultsmentioning
confidence: 86%
“…The effects of the initial Cu 2+ ion concentration on the adsorption capacity of wool keratin modified Fe 3 O 4 powders were determined by adding 0.05 g powders in a series of flasks containing 50 mL Cu 2+ ion solution with various concentrations (5,10,20,30,40, and 50 mg/L) at pH 5. After 90 min adsorption under 293, 303, 313, and 323 K conditions respectively, the supernatants were collected by centrifugation and the residual Cu 2+ ion concentrations were measured.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The adsorption kinetic behaviors of Cu 2+ ions on the wool keratin modified Fe 3 O 4 powders were determined by using the pseudo-first-order kinetic, pseudo-second-order kinetic, and intra-particle diffusion models, respectively. A total of 0.05 g of powders was placed in a series of flasks containing 50 mL Cu 2+ ion solution at a certain initial concentration (5,10,20,30,40, and 50 mg/L) and a temperature of 293 K. The supernatant in each flask was collected by centrifugation at specific time and the residual Cu 2+ ion concentration was measured. The fitting adsorption models under different initial Cu 2+ ion concentration conditions were shown in Supplementary Materials Figure S4.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation